Scheduling algorithms for routine maintenance of roads in maintenance wards of a gravel road network - Burger, A. F. (Adriaan Francois) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--University of Stellenbosch, 2005.